Some triterpenoids and steroids from Bruguiera cylindrica leaves collected from Can Gio mangrove forest - Huong Que, Nguyen Thi; Chi, Tran Minh; Kim Tuyen, Pham Nguyen; Phi Phung, Nguyen Kim (Vietnam Journal of Chemistry, 2017)
Bruguiera cylindrica (Rhizophoracea), distributed in the Southeast Asia, has been used as a traditional medicine in the treatment of diarrhea and healing of wounds. Some triterpenoids and steroids were isolated from the dried leaves of Bruguiera cylindrica, collected at Can Gio mangrove forest, Ho Chi Minh City, including lupeol (1), 3β-hydroxyoleana-9(11),12-diene (2), a mixture of stigmasterol (3a) and b-sitosterol (3b), cholesta-4-ene-3-one (4) and 3β-hydroxycholesta-5-ene-7-one (5). Their chemical structures were elucidated by spectroscopic analysis as well as comparing their data with the ones in the literature. Although these compounds were known in other plants this is the first time they are reported in this species. Keywords. Bruguiera cylindrica, triterpenoids, steroids.